
COMMENTS

Let b_n(i) be defined as for sequence A097357. Then A097357(n) = sum(i=0...infty)b_n(i) = sum(i=1...n)b_n(i). We have: Stage 1: (1,0,0,0,0,0,0,0,0,0,0,0,0) = b_1 (disregarding initial 0); Stage 2: (1,1,0,0,0,0,0,0,0,0,0,0,0,) = b_2 (disregarding initial 0); Stage 3: (0,0,1,0,0,0,0,0,0,0,0,0,0,) = b_3 (disregarding initial 0); Stage 4: (0,1,1,1,0,0,0,0,0,0,0,0,0,) = b_4 (disregarding initial 0); Stage 5: (1,0,1,0,1,0,0,0,0,0,0,0,0,) = b_5 (disregarding initial 0); Stage 6: (1,0,1,0,1,1,0,0,0,0,0,0,0,) Stage 7: (1,0,1,0,0,0,1,0,0,0,0,0,0,) Stage 8: (1,0,1,1,0,1,1,1,0,0,0,0,0,) a(n) is defined as the number which results from interpreting the sequence b_n as a binary string read backwards from the first nonzero term.
